Global marketing - Hollensen, Svend (Harlow, England ; New York : Pearson, 2020)
"Globalization is the growing interdependence of national economies - involving primarily customers, producers, suppliers and governments in different markets. Global marketing therefore reflects the trend of firms selling and distributing products and services in many countries around the world"--
Includes bibliographical references and index.
Keywords: Export marketing; Export marketing -- Case studies